The Relationship between Insulin PSTI Polymorphism and Prostate Cancer in Turkish Population - Muslumanoglu, Muhammed Hamza; Basmaci, Tanju; Ulusal, Selma Demir; Aslan, Huseyin; Tepeli, Emre; Ozdemir, Muhsin; Turgut, Mehmet (CUKUROVA UNIV, FAC MEDICINE, 2013)
Purpose: There is positive correlation between insulin and various cancers such as colon, lung and endometrium. Protate cancer is the one of them. The aim of this study, to determine the incidance of INS+1127 PstI polymorphism, located in the 3' UTR of insulin gene, between prostate cancer cases and controls and to clarify if this polymorphism have any role in the etiology of prostate cancer. Methods: We investigated 71 prostate cancer cases and 119 normal controls unrelated to patients. INS+1127 PstI polymorphism was investigated with PCR and RFLP method. Results: At the end of study; INS+1127 PstI polymorphism genotypes out to be 67.6 % CC, 28.2 % CT, 4.2 % TT among prostatic cancer individuals and 78.2% CC, 21% CT, 0.8% TT among control group individuals. Conclusion: As a result, there was no significant difference between patients and control group, in the genotype distribution.
Keywords: INS; polymorphism; prostate cancer; PSTI; General & Internal Medicine